PENGELOLAAN BADAN USAHA MILIK DESA AMANAH SEJAHTERA DI DESA SUNGAI BULUH KECAMATAN SINGINGI HILIR KABUPATEN KUANTAN SINGINGI - Saputra, Rio; SD, Zaili Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
BUMDes Amanah Sejahtera, which is one of the village business institutions in Kuantan Singingi, has succeeded in strengthening the village economy by utilizing the existing village potential. The role of the Sungai Buluh Village government in its management is very important in providing services to the community, so that BUMDes Amanah Sejahtera is able to provide optimal services and has provided independence for the village. To see how the management is, the writer uses the theory of Management by Purnomo in (Widiastuti 2019) with a qualitative method. The results showed that the things that influence the success of BUMDes management in Sungai Buluh Village are: Characteristics of the BUMDes Director, community trust, and human resources. Keywords: Management, BUMDes, Village Economy